Inhaled Nitric Oxide Augments Left Ventricular Assist Device Capacity by Ameliorating Secondary Right Ventricular Failure. Issue 4 (July 2015) - Lovich, Mark A.; Pezone, Matthew J.; Wakim, Matthew G.; Denton, Ryan J.; Maslov, Mikhail Y.; Murray, Michael R.; Tsukada, Hisashi; Agnihotri, Arvind K.; Roscigno, Robert F.; Gamero, Lucas G.; Gilbert, Richard J.
Abstract : Clinical right ventricular (RV) impairment can occur with left ventricular assist device (LVAD) use, thereby compromising the therapeutic effectiveness. The underlying mechanism of this RV failure may be related to induced abnormalities of septal wall motion, RV distension and ischemia, decreased LV filling, and aberrations of LVAD flow. Inhaled nitric oxide (NO), a potent pulmonary vasodilator, may reduce RV afterload, and thereby increase LV filling, LVAD flow, and cardiac output (CO). To investigate the mechanisms associated with LVAD-induced RV dysfunction and its treatment, we created a swine model of hypoxia-induced pulmonary hypertension and acute LVAD-induced RV failure and assessed the physiological effects of NO. Increased LVAD speed resulted in linear increases in LVAD flow until pulse pressure narrowed. Higher speeds induced flow instability, LV collapse, a precipitous fall of both LVAD flow and CO. Nitric oxide (20 ppm) treatment significantly increased the maximal achievable LVAD speed, LVAD flow, CO, and LV diameter. Nitric oxide resulted in decreased pulmonary vascular resistance and RV distension, increased RV ejection, promoted LV filling and improved LVAD performance. Inhaled NO may thus have broad utility for the management of biventricular disease managed by LVAD implantation through the effects of NO on LV and RV wall dynamics.